228k views
5 votes
i dont know how to do this and there are multiple questions, so in total 4. if you dont mind being able to answer questions for a little less than a while, than please help. thank you.

i dont know how to do this and there are multiple questions, so in total 4. if you-example-1

1 Answer

5 votes

We can do the following steps to solve the equation.

Step 1: We apply the distributive property. For this, the number outside the brackets is multiplied by everything that is inside the brackets.

Then, we have:


\begin{gathered} (5)/(4)(x-(8)/(5))=13 \\ (5)/(4)\cdot x-(5)/(4)\cdot(8)/(5)=13 \\ (5)/(4)x-(5\cdot8)/(4\cdot5)=13 \\ (5)/(4)x-(8)/(4)=13 \\ (5)/(4)x-2=13 \end{gathered}

Step 2: We add 2 from both sides.


\begin{gathered} (5)/(4)x-2=13 \\ (5)/(4)x-2+2=13+2\rbrack \\ (5)/(4)x=15 \end{gathered}

Step 3: We multiply by 4 from both sides.


\begin{gathered} 4\cdot(5)/(4)x=15\cdot4 \\ 5x=60 \end{gathered}

Step 4: We divide by 5 from both sides.


\begin{gathered} (5x)/(5)=(60)/(5) \\ x=12 \end{gathered}

Therefore, the value of x is 12.

i dont know how to do this and there are multiple questions, so in total 4. if you-example-1
User Vivek Vermani
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.